Transformation of Employment Structures in Poland - Servitization of Economy - Kotlorz, Dorota; Skórska, Anna (Olsztyn Economic Journal, 2013)
Transformation of the Polish economy and the related process of reallocation of labour resources have been progressing since the beginning of the 1990s, but their growth is insufficient. The current level of development of the service sector does not constitute an adequate alternative to diminishing employment in the so-called declining heavy industries, which were dominant in the Polish economy for many years. Given that a more dynamic growth in the services sector can contribute to the labour market balancing alleviating the unemployment problem, not only by the absorption of people laid off from the restructuring industrial enterprises but also by providing new jobs for young people, it is necessary to increase consistently the share of modern section services in GDP and total employ-ment.Increasing employment and created added value in modern, knowledge-based services are consistent with the direction of changes observed in the developed countries.In Poland, the employment is steadily increasing in services related to real estate and businesses, financial and insurance services, particularly in IT services. The knowledge embodied in products and technologies and highly skilled labour resources determines the innovativeness of the economy, providing a source of growth and competitiveness. Therefore, the direction and pace of these changes are important.One of the possibilities of further service sector development in Poland is the offshoring of business services. The created BPO and KPO centres allow for the absorption of high-quality labour resources, including university graduates, whose numbers are increasing from year to year. This is even more important as in the long time span the sector development and created jobs will increasingly be based on the human factor and the skills possessed by employees rather than on lower labour costs compared with other locations.